(untitled) (Research, Society and Development, 2022)
The objective of this work is to approach about fraud in the scope of Brazilian law. For the study, it is necessary to proceed with the due distinction of what is classified as fraud in the scope of procedural law, that is, fraud in the process, as well as, what is considered and classified as fraud in substantive law, directly linked to the obligations governed by civil law. It is important that such a definition is made so that it is possible, within the scope of the legal debate, to define the applicable rule and the way to proceed, if the fraud envisaged is procedural or material fraud, understanding that this classification will determine whether the fraud is against execution or against creditors, an important differentiation for legal treatment. Recognizing fraud and its classification in the legal environment is necessary so that it is possible to reprimand the illicit act and undo operations that aim to circumvent the law and harm legitimate creditors, through incisive action by the Judiciary.